2020
DOI: 10.1186/s40364-020-00203-6
|View full text |Cite
|
Sign up to set email alerts
|

The emerging roles of N6-methyladenosine RNA methylation in human cancers

Abstract: N6-methyladenosine (m6A) is the most abundant form of mRNA modification in eukaryotes. It affects various aspects of RNA metabolism, including nuclear export, translation, decay and alternative splicing. In addition, m6A also participates in a great number of human physiological processes, ranging from spermatogenesis modulation, response to heat shock, the control of T cell homeostasis to stem cell proliferation and differentiation. The dynamic equilibrium of m6A level is regulated by m6A methyltransferases (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 132 publications
0
33
0
1
Order By: Relevance
“…Nükleobaz metilasyonu tek bir metilasyon tepkimesi ile sınırlı değildir; aynı konumun (exN konumu için mümkün olan metil-6-Adenozin) veya farklı konumların (metil2-metil8-Adenozin) çift metilasyon örnekleri bilinmektedir [15][16] . RNA cap'te metil-2,2,7Guanozin olduğu gibi üçlü metilasyon da meydana gelebilir 17 .…”
Section: Rna'daki Enzimatik Nükleobaz Metilasyonlarıunclassified
“…Nükleobaz metilasyonu tek bir metilasyon tepkimesi ile sınırlı değildir; aynı konumun (exN konumu için mümkün olan metil-6-Adenozin) veya farklı konumların (metil2-metil8-Adenozin) çift metilasyon örnekleri bilinmektedir [15][16] . RNA cap'te metil-2,2,7Guanozin olduğu gibi üçlü metilasyon da meydana gelebilir 17 .…”
Section: Rna'daki Enzimatik Nükleobaz Metilasyonlarıunclassified
“…Recently, N(6)-methyladenosine (m 6 A) modification in mRNA or lncRNA functionally modulate the RNA splicing, localization, stability, and ceRNA activity. 15,16 We performed methylated RNA immunoprecipitation (MeRIP) assays in Caski and Hela cells and found that ZFAS1 could be significantly enriched by m 6 A antibody compared to IgG (Figure 5A). The m 6 A modification sites of ZFAS1 was predicted by SRAMP online tool (www.cuilab.cn) (Supplemental Table 1).…”
Section: Zfas1 Sequestered Mir-647 In a M 6 A-dependent Mannermentioning
confidence: 99%
“…In addition, specific RNA-binding proteins that recognize m6A and affect the fate of RNAs are grouped as m6A readers, such as the YTH domain family of proteins [ 14 ] and IGF2BP proteins [ 15 ]. Currently, m6A has emerged as a widespread regulatory mechanism that controls gene expression [ 16 ].…”
Section: Introductionmentioning
confidence: 99%